Percepción y expectativas frente al servicio de formación deportiva ofrecido por la Escuela Talentos Lideres en período pos pandemia (2024)
The research project focuses on the Sports Training School "Talentos Líderes," where it has been observed that, following the global health crisis of COVID-19, all activities, including sports, were affected. This led to health problems such as obesity, diabetes, and heart diseases. Containment measures, such as the closure of school sports centers and the suspension of youth activities and sports, have made it difficult for children and adolescents to reach recommended levels of physical activity, increasing stress and anxiety levels in all individuals, including the younger ones. The research aims to analyze the perception and expectations of parents and children regarding the training service offered by the school in the post-pandemic period. The goal is to describe how parents and children perceive this service in order to understand their expectations. This will enable the design of strategies to improve the service and foster the trust of parents and teenagers in the activities carried out in the training school. Methodologically, the research used a qualitative approach, based on the case study method where the interview was used as a data collection technique. The results showed, in general, a positive perspective of parents and children regarding the quality of service in sports training provided by the school. The trust and timely response to the children's needs stand out, as well as the training, experience and empathy that the trainers have to develop the work plan with the children. Among the opportunities for improvements identified by parents and children, elements related to the physical infrastructure of the scenarios and some particular points of the training were found. Clear strategies and actions were left for the school to overcome these barriers.